Les négociations des travailleurs de l'économie informelle - Verena Schmidt; Edward Webster; Siviwe Mhlana; Kally Forrest (Organisation internationale du Travail, 2023)
Negotiations are a valuable and important tool for increasing the voice of workers in the informal economy. This paper provides empirical evidence from Africa, Asia and the Americas on negotiations and collective bargaining by workers in the informal economy. These practices demonstrate that negotiations involving workers in the informal economy, including those that culminate in collective agreements, are key to ensuring the fair distribution of the fruits of economic progress and labour protection to workers in many countries. They are also an important tool for reducing informalization trends. The paper also shows the multiple challenges workers in the informal economy are facing when organizing and entering into negotiations and outlines some possible pathways on how these can be reduced.
Keywords: 330; informal employment; self employment; labour relations; collective bargaining; workers representation; informal economy; nongovernmental organizations